The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1021/la7021165
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Degradation of Orange II on Different Iron (Hydr)oxides in Aqueous Suspension:  Rate Enhancement on Addition of Hydrogen Peroxide, Silver Nitrate, and Sodium Fluoride

Abstract: Photoinduced organic oxidation with iron (hydr)oxides in aqueous suspension has been argued with respect to two principal mechanisms: (a) photoinduced ligand-to-metal charge transfer within a surface complex and (b) semiconductor photocatalysis. In this work, the photodegradation of azo dye orange II with UV light (lambda > or = 320 nm) in the aerated aqueous suspensions of haematite, maghemite, magnetite, goethite, lepidocrocite, and feroxyhite at an initial pH of 6.5 has been examined. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 32 publications
9
74
1
1
Order By: Relevance
“…-FeOOH and its poorly natural counterpart, feroxyhyte ('-FeOOH), have structures based on the CdI 2 and disordered CdI 2 models, respectively [45]. They have received also little attention since Fe oxides (magnetite, maghemite and hematite) have shown to be more active than Fe (hydr)oxides in the studies carried out so far [45,53]. Table 2 summarizes the work done on the application of magnetite-based natural minerals in CWPO up to now.…”
Section: Magnetic Natural Mineralsmentioning
confidence: 99%
“…-FeOOH and its poorly natural counterpart, feroxyhyte ('-FeOOH), have structures based on the CdI 2 and disordered CdI 2 models, respectively [45]. They have received also little attention since Fe oxides (magnetite, maghemite and hematite) have shown to be more active than Fe (hydr)oxides in the studies carried out so far [45,53]. Table 2 summarizes the work done on the application of magnetite-based natural minerals in CWPO up to now.…”
Section: Magnetic Natural Mineralsmentioning
confidence: 99%
“…To improve the microbial quality of the water, it would be desirable to couple virus adsorption with inactivation. Several studies have shown that the irradiation of iron oxides with sunlight leads to the degradation of organic contaminants, in particular if the contaminants are adsorbed onto the iron oxide surface (Andreozzi et al, 2003;Du et al, 2008).…”
Section: Combination Of Adsorption and Sunlight Exposure Enhances Losmentioning
confidence: 99%
“…Iron oxides are semiconductors capable of producing oxidants when irradiated with sunlight (Andreozzi et al, 2003;Du et al, 2008). They can also participate in photo-Fenton reactions leading to the production of hydroxyl radicals (He et al, 2002), which cause virus inactivation (Nieto-Juarez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…From these results, together with the low, albeit signicant, degradation speeds, we infer that the degradation reaction is primarily governed by other properties of the hematite cubes. Considering that hematite is a known photocatalyst, 32,35,37,46,47 we investigated the inuence of active illumination with visible and UV light.…”
Section: -22mentioning
confidence: 99%